Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - 8-8 Factoring by Grouping - Practice and Problem-Solving Exercises: 21

Answer

$(3y+1)(4y^{2}-3)$

Work Step by Step

$12y^{3}=2.2.3.y.y.y$ and $4y^{2}=2.2.y.y$ Hence, $GCF=$$2.2.y.y=4y^{2}$ $9y=$$3.3.y$ and $3=3.1$ Hence, $GCF=3$ After grouping; $=(12y^{3}+4y^{2})-(9y+3)$ $=4y^{2}(3y+1)-3(3y+1)$ $=(3y+1)(4y^{2}-3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.